Correlation between Retinal Changes and Visual Function in Late-Stage Vogt-Koyanagi-Harada Disease: An Optical Coherence Tomography Study - Min Zhou; Chunhui Jiang; Ruiping Gu; Zhongcui Sun; Nancy Huynh; Qing Chang (Journal of Ophthalmology)
Purpose. To characterize the optical coherence tomography (OCT) findings in late-stage Vogt-Koyanagi-Harada (VKH) disease and its correlation with visual function. Methods. The records of patients with late-stage VKH disease (defined as ≥12 months from disease onset) were retrospectively reviewed. The analysis focused on the OCT findings and microperimetry, in addition to the possible correlation between morphology and functional findings. Results. Twenty-nine patients (58 eyes) were included. Mean age at onset was 34.24 ± 10.67 years. The OCT revealed that the outer retina and retinal pigment epithelium (RPE) were mainly affected. These effects included RPE thickening and breakage or disappearance of the cone outer segment tip (COST) line and/or inner segment/outer segment (IS/OS) junction. The COST line and IS/OS results were related to macular function and the interval between symptom onset and initiation of high-dose corticosteroid treatment (all P<0.01). Eyes with intact COST lines demonstrated intact IS/OS and normal RPE layers as well as better visual function and normal retinal sensitivity. Conclusions. The OCT findings are strongly correlated with macular function, as well as other clinical findings in late-stage VKH. With respect to the COST line and retinal sensitivity especially, the OCT and microperimetry findings may be useful for evaluating later-stage VKH.